A simple electrochemiluminesecence aptasenor using a GCE/NCQDs/aptamers for detection of Pb. Issue 15 (3rd July 2022) - Li, Danyang; Chen, Chi; Guo, Xuefei; Liu, Changxia; Yang, Wensheng
ABSTRACT: An electrochemiluminescence (ECL) aptasensor was prepared to detect Pb 2+ with nitrogen-doped carbon quantum dots (NCQDs) as ECL materials. To prepare the working electrode, NCQDs with carboxyl groups were loaded on a glassy carbon electrode (GCE) and then Pb 2+ aptamers were covalently bound to the NCQDs to form a stable GCE/NCQDs/aptamers. On addition of Pb 2+, the chain aptamers change to a pb 2+ G-quadruplex conformation, which lead to a large decrease in the ECL intensity. The variation of intensity and the logarithm of the Pb 2+ concentration had a good linear relationship ( R 2 = 0.998). The detection range was wide (50 pM to 387.9 nM) with a low detection limit (18.9 pM). In interference experiments, the ECL Pb 2+ aptasensor did not suffer from interference and it had good stability. The NCQDs ECL aptasensor can detect Pb 2+ quickly and accurately, and provides a fast and efficient method for detection of Pb 2+ . Compared with literatures, the Pb 2+ aptasensor has simpler preparation process, lower cost; furthermore, it is more environmentally friendly. GRAPHICAL ABSTRACT: UF0001